Ramelteon for Delayed Sleep-wake Phase Disorder: A Case Report - Takeshima, Masahiro (Clin Psychopharmacol Neurosci, 2020)
Recently developed melatonin receptor agonists are expected to be effective for delayed sleep-wake phase disorder (DSWPD). To date, however, no study has described the effect of melatonin receptor agonists on DSWPD. We report the case of a 15-year-old girl with DSWPD who was successfully treated with ramelteon 4 mg at 7 pm. DSWPD symptoms were resolved; her sleep-wake and biological rhythms were normalized.